DESIGN AND PERFORMANCE TEST OF AUTOMOTIVE MAGNETO-RHEOLOGICAL FLUID CLUTCH - CHEN DeMin; ZHANG Hong; CAI QingGe; LIU GuoQiang; WU JiaXi (Jixie qiangdu)
Automotive Magneto-rheological Fluid Clutch（ MFC） is a new clutch that combines smart material,or Magnetorheological Fluid,and design of automobile clutch. Based on the Bingham model,the expressions of transmission torque for discshaped MFC were established. We design and process a sample machine to test the capability,stability of torque as well as performances of connection and separation. In addition,influences of magnetic saturation and residual magnetism to speeds of connection and separation also have been analyzed. The testing results indicate that the performance of MFC can meet the need of design and use.